Do numbers speak for themselves? Exploring the use of quantitative data to measure policy 'success' in historical Indigenous higher education in the Northern Territory, Australia. Issue 3 (16th April 2022) - Street, C.; Guenther, J.; Smith, J.; Robertson, K.; Ludwig, W.; Motlap, S.; Woodroffe, T.; Ober, R.; Gillan, K.; Larkin, S.
ABSTRACT: 'The numbers speak for themselves' is a phrase often linked to statistics supporting claims about the success (or otherwise) of policies. Quantitative data are usually viewed as objective and somehow exempt from the same critique that qualitative data faces. QuantCrit theory challenges these assumptions by considering how structural racism impacts on the use of statistics in research and evaluation. This paper applies QuantCrit to the Indigenous higher education policy context in the Northern Territory (NT), Australia. It aims to elicit hidden assumptions within the use of statistics to measure the success of Indigenous higher education policies in the NT. We explore the historical utility of Indigenous higher education student statistics for policy evaluation in the NT. We argue that quantitative success measures should always be considered within the context of the structural racism that shapes policy goals. We conclude by highlighting that quantitative data can be useful for Indigenous higher education policy evaluation and research, but that alternative views for measuring policy success must be considered.